Pengaruh Kompensasi dan Motivasi terhadap Kinerja Pegawai Negeri Sipil dengan Kepuasan Kerja sebagai Variabel Intervening - Mundakir Mundakir; Mohammad Zainuri (Universitas Muria Kudus, 2018)
This study was conducted to analyze the effect of compensation and motivation on employee performance with job satisfaction as an intervening variable. The research method used is quantitative method. Research respondents are employees of Public Works Department of Rembang Regency with a sample of 162 employees. Data is collected using questionnaire instruments. Statistical tests and data processing were performed using SEM Analythic. The results of the study indicate that compensation and work motivation have effect on employee job satisfaction. Direct compensation has no effect on employee performance. While work motivation and job satisfaction have a significant effect on employee performance. Compensation and work motivation indirectly through job satisfaction have a significant effect on employee performance.